Beyond the master's tools? decolonizing knowledge orders, research methods and teaching - Ziai, Aram; Bendix, Daniel; Muller, Franziska (KILOMBO: International Relations and Colonial Questions, 2020)
"This book provides a compendium of strategies for decolonizing global knowledge orders, research methodology and teaching in the social sciences. The volume presents recent work on epistemological critique informed by postcolonial thought, and outlines strategies for actively decolonizing social science methodology and learning/teaching environments that will be of great utility to IR and other academic fields that examine global order. The volume focuses on the decolonization of intellectual history in the social sciences, followed by contributions on social science methodology and lastly more practical suggestions for educational/didactical approaches in academic teaching. The book is not confined to the classical format of research articles but moves beyond such boundaries by bringing in spoken word and interviews with scholar-activists. Overall this volume enables researchers to practice a reflexive and situated knowledge production more suitable to confronting present-day global predicaments. The perspectives mobilise a constructive critique, but also allow for a reconstruction of methodologies and methods in ways that open up new lenses, new archives of knowledges and reconsider the who, the how and the what of the craft of social science research into global order"